Bitter Orange Tree - Alharthi, Jokha; Booth, Marilyn (New York: Catapult, 2022)
"Bitter Orange Tree is a profound exploration of social status, wealth, desire, and female agency by Jokha Alharthi. It presents a mosaic portrait of one young woman's attempt to understand the roots she has grown from, and to envisage an adulthood in which her own power and happiness might find the freedom necessary to bear fruit and flourish. Zuhour, an Omani student at a British university, is caught between the past and the present. As she attempts to form friendships and assimilate in Britain, she can't help but ruminate on the relationships that have been central to her life. Most prominent is her strong emotional bond with Bint Amir, a woman she always thought of as her grandmother, who passed away just after Zuhour left the Arabian Peninsula. As the historical narrative of Bint Amir's challenged circumstances unfurls in captivating fragments, so too does Zuhour's isolated and unfulfilled present, one narrative segueing into another as time slips and dreams mingle with memories"--
In English, translated from the Arabic.
Keywords: Immigrants -- England -- Fiction; Granddaughters -- Fiction; Muslim women -- Fiction; Dreams -- Fiction; Loneliness; Domestic fiction